Very Special Relativity Models: Infrared Regularization and Loop Corrections - Jorge Alfaro (Axioms, 2025)
We review the <semantics>Sim(2)</semantics> invariant infrared regularization of Very Special Relativity models that we have proposed recently and apply it to compute loop corrections in quantum electrodynamics with VSR masses for neutrino and photon. Then, we compute the axial anomaly. Finally, we study the Gross–Neveu model with a VSR mass in the large N limit uncovering a new phase of the model.